2021
DOI: 10.3390/ijerph18052209
|View full text |Cite
|
Sign up to set email alerts
|

How Can Bullying Victimisation Lead to Lower Academic Achievement? A Systematic Review and Meta-Analysis of the Mediating Role of Cognitive-Motivational Factors

Abstract: Bullying involvement may have an adverse effect on children’s educational outcomes, particularly academic achievement. However, the underlying mechanisms and factors behind this association are not well-understood. Previous meta-analyses have not investigated mediation factors between bullying and academic achievement. This meta-analysis examines the mediation effect of cognitive-motivational factors on the relationship between peer victimization and academic achievement. A systematic search was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 88 publications
5
32
0
1
Order By: Relevance
“…Other expected results of this study highlight age-related differences in school achievement: secondary school students had lower grades and more absences, because of change in the school climate and increasing challenges related to the more complex and difficult school tasks (Butnaru & Gherasim, 2014). The negative effects of bullying and victimization documented by empirical studies (Lodder et al, 2016, Blakely-McClure & Ostrov, 2016 and meta-analyses in this field (Samara et al, 2021) are confirmed through our data which indicated that bullies had lower school achievement and they miss several days from school than their colleagues. In our sample, victimization correlated negatively with achievement in language.…”
Section: Statistical Analysessupporting
confidence: 80%
See 1 more Smart Citation
“…Other expected results of this study highlight age-related differences in school achievement: secondary school students had lower grades and more absences, because of change in the school climate and increasing challenges related to the more complex and difficult school tasks (Butnaru & Gherasim, 2014). The negative effects of bullying and victimization documented by empirical studies (Lodder et al, 2016, Blakely-McClure & Ostrov, 2016 and meta-analyses in this field (Samara et al, 2021) are confirmed through our data which indicated that bullies had lower school achievement and they miss several days from school than their colleagues. In our sample, victimization correlated negatively with achievement in language.…”
Section: Statistical Analysessupporting
confidence: 80%
“…Based on previous empirical studies on the negative effects of bullying on short and long-term achievements, meta-analyses by Samara et al (2021) andTtofi et al (2011) point out the increased short-term risks of bullying like school absenteeism, truancy and dropout rate for the students who perceive the school as an unsafe place and also, long-term risk of bullying to develop adverse outcomes, later in their life. Ttofi et al (2011) endorse the importance of quality anti-bullying prevention programs to interrupt future criminal careers.…”
Section: Effects Of Bullying On Educational Outcomesmentioning
confidence: 99%
“…Understanding that children's selfesteem and bullying does play a role in their achievement and that intervening these may have impact on emotional states and symptoms (Kretschmer, 2016), but also on their achievement. Working on improving children's self-esteem and decreasing bullying experiences can also be seen as a first step when planning achievement interventions (Samara et al, 2021). As we included 8-12-year-old children, our results can be used to design interventions that directly target bullying and self-esteem in primary school, enabling schools, policy makers, clinicians, and caregivers to provide adequate support to children.…”
Section: Discussionmentioning
confidence: 99%
“…Socially isolated children and youth also suffer considerably; they too have poorer physical (Gini and Pozzoli 2013) and mental health (Moore et al 2017;Mulvey et al 2018). They also tend to have lower academic achievement (Samara et al 2021;Wentzel et al 2021) than children and youth who are more socially integrated. Thus, because relationships matter for health and learning, the COVID-19 school closures undertaken in certain provinces, are untenable, and are, in fact, causing harm (Science et al 2021).…”
Section: Social Isolation and Loneliness Pre-covid-19mentioning
confidence: 99%
“…A positive school climate is consistently associated with better academic achievement (Catalano et al 2004;Osher and Kendziora 2010;Bryan et al 2012;Niehaus et al 2012;Wang et al 2014;Konold et al 2018;Daily et al 2019), better mental health (Somersalo et al 2002;Shochet et al 2006;Suldo et al 2012;Aldridge and McChesney 2018), and better peer relationships (Low and Van Ryzin 2014;Konishi et al 2017). These associations are interconnected-poor school climate is related to higher rates of bullying victimization (Wang et al 2014), which is associated with lower academic achievement (Samara et al 2021), and is causally linked to poor mental health (Moore et al 2017). Bullying is a notable problem for children and youth worldwide.…”
Section: The First R Of Education-relationshipsmentioning
confidence: 99%